Evaluation of mineral content in healthy permanent human enamel by Raman spectroscopy - Akkus, Anna; Akkus, Asya; Roperto, Renato; Akkus, Ozan; Porto, Thiago [UNESP]; Teich, Sorin; Lang, Lisa (Medicina Oral, S.L., 2016)
Background: An understanding of tooth enamel mineral content using a clinically viable method is essential since variations in mineralization may serve as an early precursor of a dental health issues, and may predict progression and architecture of decay in addition to assessing the success and effectiveness of the remineralization strategies. Material and Methods: Twenty two human incisor teeth were obtained in compliance with the NIH guidelines and site specifically imaged with Raman microscope. The front portion of the teeth was divided into apical, medium and cervical regions and subsequently imaged with Raman microscope in these three locations. Results: Measured mineralization levels have varied substantially depending on the regions. It was also observed that, the cervical enamel is the least mineralization as a populational average. Conclusions: Enamel mineralization is affected by a many factors such as are poor oral hygiene, alcohol consumption and high intake of dietary carbohydrates, however the net effect manifests as overall mineral content of the enamel. Thus an early identification of the individual with overall low mineral content of the enamel may be a valuable screening tool in determining a group with much higher than average caries risk, allowing intervention before development of caries. Clinically applicable non-invasive techniques that can quantify mineral content, such as Raman analysis, would help answer whether or not mineralization is associated with caries risk.
Keywords: Dental caries; Enamel; Mineral content; Raman spectroscopy